Invisible dark matter decays of a non-Standard Model like CP-even scalar boson - Maien Binjonaid (Journal of King Saud University: Science, 2024)
We investigate two extensions of the standard model that include particle dark matter candidates: the Next-to-Two Higgs Doublet Model and the Next-to-minimal Supersymmetric Standard Model. These models feature a non-Standard Model like CP-even scalar with a sub-TeV mass, denoted by H2, among other particles. At a 13 TeV proton–proton collider, the primary production channel for such scalars is via the fusion of a pair of gluons. Subsequently, these scalars can decay invisibly into a pair of dark matter candidates, which can be dominant. In the supersymmetric model, it is possible for the Lightest Supersymmetric Particle (LSP) and Next-to Lightest Supersymmetric Particle (NLSP) to be mass degenerate, leading to quasi-invisible H2 decays to LSP+NLSP and NLSP+NLSP. We present the predictions of both models for this challenging scenario while ensuring compatibility with recent experimental constraints.